Led Light Computer Simulation and Design on Solar Battery - I.I, Bayneva (International Journal of Engineering and Technology, 2018)
The article considered the features of architectural lighting and lighting devices. They analyzed the requirements for architectural luminaires and their features, solar elements, their operation principle and design. They described the developed luminaire, its design and light sources and the device electronic elements. The modeling of lamp light distribution and illumination is car-ried out.Â Â Â